Perancangan Sistem Informasi Persediaan Obat Pada Klinik Medika Prima Berbasis Web Menggunakan Metode Waterfall - Yolanda Anggraini; Rizki Fadillah; Nuryanti Tuto Suban; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
Medika Prima Clinic is a public clinic established by the Medika Prima Utama Foundation and has an operational license since 2015. The clinic is located at Jl. Raya Ciomas No.290, Ciomas Rahayu, Ciomas sub-district, Bogor Regency, West Java. Based on interviews, information was obtained that there are obstacles, namely that it takes longer to complete the process of searching for drug data, irregular storage of drug inventory data causes frequent loss and damage of documents, and the preparation of drug data reports is still done manually, making it difficult for the data analysis process and producing less accurate data. Based on these problems, the purpose of this study is to develop a web-based drug supply information system that will facilitate drug searches, store drug supply data, and report drug supply data that can be well organized and accurate. The information system created using the web-based waterfall method with the PHP programming language and using the MySql database. the waterfall method is the traditional life cycle includes a software development methodology. which emphasizes a logical and systematic process system testing is carried out to ensure good performance and functionality. trials were carried out involving users and utilizing original drug data. The test results show that the Medika Prima Clinic web-based drug inventory information system can effectively manage drug inventory and improve the efficiency of drug stock management.